Analysts' Forecasts, Earnings, Variability, and Option Pricing: Empirical Evidence. - Daley, Lane A.; Senkow, David W.; Vigeland, Robert L. (The Accounting Review, 1988)
Abstract ABSTRACT: This study investigates empirical relations that are consistent with the hypothesis that variance in analysts' forecasts of earnings (i.e., disagreement among analysts) is useful as an ex ante measure of the market's aggregate uncertainty regarding a future earnings signal. We hypothesize and test for a positive association between the variance of analysts' forecasts and (1) the ex post magnitude of unexpected earnings. (2) the ex post variance of returns around the actual earnings announcement date. and (3) the average variance of return to maturity implied by prices of options maturing after the earnings announcement date. Our results generally confirm that the disagreement among analysts' earnings forecasts Is a useful Indicator of the market's aggregate uncertainty regarding future earnings announcements.